Thymosin β4 Improves Differentiation and Vascularization of EHTs - Tilman Ziegler; Rabea Hinkel; Andrea Stöhr; Thomas Eschenhagen; Karl-Ludwig Laugwitz; Ferdinand le Noble; Robert David; Arne Hansen; Christian Kupatt (Stem Cells International)
Induced pluripotent stem cells (iPSC) constitute a powerful tool to study cardiac physiology and represents a promising treatment strategy to tackle cardiac disease. However, iPSCs remain relatively immature after differentiation. Additionally, engineered heart tissue (EHT) has been investigated as a therapy option in preclinical disease models with promising results, although their vascularization and functionality leave room for improvement. Thymosin β4 (Tβ4) has been shown to promote the differentiation of progenitor cell lines to cardiomyocytes while it also induces angiogenic sprouting and vascular maturation. We examined the potential impact of Tβ4 to enhance maturation of cardiomyocytes from iPSCs. Assessing the expression of transcription factors associated with cardiac differentiation, we were able to demonstrate the increased generation of cells displaying cardiomyocyte characteristics in vitro. Furthermore, we demonstrated, in a zebrafish model of embryonic vascular development, that Tβ4 is crucial for the proper execution of lymphatic and angiogenic vessel sprouting. Finally, utilizing Tβ4-transduced EHTs generated from mice genetically engineered to label endothelial cells in vitro, we show that treatment with Tβ4 promotes vascularization and contractility in EHTs, highlighting Tβ4 as a growth factor improving the formation of cardiomyocytes from iPSC and enhancing the performance of EHTs generated from neonatal cardiomyocytes.